2018
DOI: 10.4401/ag-7711
|View full text |Cite
|
Sign up to set email alerts
|

Ambient noise measurements for preliminary microzoning studies in the city of Messina, Sicily

Abstract: On December 28 th 1908 the city of Messina was destroyed by one of the most catastrophic Italian earthquakes of the last centuries (M w =7.1, I = XI) which caused more than 60000 deaths and destruction in many localities of Sicily and Calabria. In this study we present the results of more than 100 seismic ambient noise measurements carried out in the framework of the first massive seismic site response survey performed in the city of Messina. Starting from geological information and historical reports reconstr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…When performed on top of partly detached blocks of the cliff face, these curves also show peaks at a higher frequency related to the vibrations of the detached blocks from the cliff. (e.g., Pino et al 2018;Pischiutta et al 2016;Scolaro et al 2018;Villani et al2018 and reference therein). Iannucci et al (2018) carried out an extensive ambient noise survey to characterize the complex landslide system in the area.…”
Section: Discussionmentioning
confidence: 99%
“…When performed on top of partly detached blocks of the cliff face, these curves also show peaks at a higher frequency related to the vibrations of the detached blocks from the cliff. (e.g., Pino et al 2018;Pischiutta et al 2016;Scolaro et al 2018;Villani et al2018 and reference therein). Iannucci et al (2018) carried out an extensive ambient noise survey to characterize the complex landslide system in the area.…”
Section: Discussionmentioning
confidence: 99%
“…The origins of ambient vibrations can be linked to both natural sources, including earthquakes, volcanoes, storms, and geothermal activities, and anthropogenic sources, such as factories, traffic, and engines. These vibrations find practical utility in various applications, such as local or regional passive seismic tomography [6,7] and engineering seismology aimed at understanding seismic site effects [8][9][10]. Additionally, they play a pivotal role in environmental seismology applications, monitoring parameters such as aquifer levels [11,12], river transportation characteristics [13,14], glacier discharge [15,16], landslides [17][18][19], and meteo-marine events associated with phenomena like "hurricane" and "microseism" [20,21].…”
Section: Introductionmentioning
confidence: 99%
“…An alternative approach to estimate the depth of the seismic bedrock and thickness of surface deposits involves the use of the horizontal-to-vertical spectral ratio (HVSR) methodology [45][46][47], which is also applied to the groundwater exploration and aquifer geometry characterization [12,41,48]. Many authors demonstrated that reliable S-wave-velocity models can be obtained by inverting HVSR data with other stratigraphic and geophysical constraints [47,[49][50][51][52]. In particular, the uncertainty about the HVSR stratigraphic interpretation [53] can be addressed or at least limited using S-wave velocity models obtained by MASW as constraints [46,47,54].…”
Section: Introductionmentioning
confidence: 99%